Frozen Section Diagnostic Pitfalls of Sertoli-Leydig Cell Tumor with Heterologous Elements - Ashley Burris; Caleb Hixson; Nathaniel Smith (Case Reports in Pathology)
A woman in her sixth decade presented with several months of abdominal cramping, decreased appetite, bloating, and increased constipation. Radiologic imaging revealed a 28 cm, multilocular, heterogeneous cystic neoplasm involving the right adnexa. An intraoperative frozen section showed mucinous glandular epithelium, with and without foci of goblet cells, embedded in apparent ovarian stroma. The findings were concerning at least borderline mucinous cystadenoma with possible invasion. Subsequent surgical management and staging were performed. Permanent sections showed a moderately to poorly differentiated Sertoli-Leydig cell tumor (SLCT) with retiform foci and heterologous elements. The discrepancy between frozen and permanent sections was attributable to solely sampling a focus of heterologous elements during intraoperative consultation. The rarity of SLCT and even rarer presence of both heterologous and retiform elements make this concerning frozen section diagnostic pitfall.